Enhancing electrocatalytic performance of RuO2-based catalysts: mechanistic insights, strategic approaches, and recent advances - Binod Raj KC; Dhananjay Kumar; Bishnu Prasad Bastakoti (JPhys Energy)
Electrochemical water splitting presents the ultimate potential of hydrogen and oxygen production; however, regulating the rate and efficiency of water splitting is highly dependent on the accessibility of extremely efficient electrode materials for slow performance kinetics and large overpotential of both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Ruthenium oxide (RuO _2 ) based materials display high performance for OER and HER because of their capacity to bind oxygen, eminent catalytic activity, low cost compared to other precious metals, and stability in a wide pH range. However, there is still much space to promote the OER and HER activity and stability of RuO _2 to fulfill the necessity for practical applications in water splitting. Different researchers applied multiple approaches that boosted the catalytic performance of RuO _2 -based electrocatalysts toward overall water splitting. Herein, this review provides a comprehensive overview of recent advancements in RuO _2 -based materials in the field of water electrolysis for the generation of alternative energies. It gives a general description of water splitting in acidic and alkaline settings, including reaction mechanisms as well as common evaluation elements for the catalytic function of the materials. Most of the reviews reported based on RuO _2 materials are only focused on OER performance, but this review highlighted comprehensive ideas on different strategies like morphology design, electronic structure, electrolytes, and compositions for optimizing both electrocatalytic HER and OER functioning of RuO _2 -based electrocatalysts.